2009
DOI: 10.1086/595737
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin Reductase Is Essential for Protection ofNeisseria gonorrhoeaeagainst Killing by Nitric Oxide and for Bacterial Growth during Interaction with Cervical Epithelial Cells

Abstract: In Neisseria gonorrhoeae, the MerR family transcription factor NmlR activates 3 operons in response to disulfide stress. In the present study, we show that trxB, a monocistronic operon under the control of NmlR, encodes a functional thioredoxin reductase. It is shown that neisserial TrxB has biochemical properties similar to those of its homologue from Escherichia coli. Analysis of a trxB mutant of N. gonorrhoeae showed that it was more sensitive to disulfide stress and to stress induced by organic hydroperoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…In earlier publications, we also showed that mutation of estD and trxB resulted in a greatly diminished ability of N. gonorrhoeae to form biofilms both on glass and over THCECs (20,21). Therefore, we evaluated biofilm formation by wild-type 1291 and 1291 copA after 2 days of growth under continuous flow (Table 1; see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In earlier publications, we also showed that mutation of estD and trxB resulted in a greatly diminished ability of N. gonorrhoeae to form biofilms both on glass and over THCECs (20,21). Therefore, we evaluated biofilm formation by wild-type 1291 and 1291 copA after 2 days of growth under continuous flow (Table 1; see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In women, gonococci are typ-ically associated with the cervical epithelium and are able to invade, survive, and replicate within these cells (4). We previously reported that inactivation of estD and trxB, two genes in the NmlR regulon, results in reduced survival of N. gonorrhoeae during challenge of cervical epithelial cells (20,21). To determine if copA is also important during cervical infection, we tested the ability of N. gonorrhoeae 1291 and 1291 copA to associate with, invade, and survive within pex cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2B, indeed, B. pertussis is rather susceptible to NO-mediated killing in vitro, because exposure to 400 mM DEANONOate as a donor of NO radicals (35,36) significantly decreased viability of the bacteria, albeit less than upon oxidative killing by 100 mM H 2 O 2 (37). As further shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance addition of NO donors was shown to induce dispersal in biofilms of P. [45] and a marine Pseudoalteromonas species [46], and in Vibrio fischeri addition of a NO scavenger prevented dispersal of aggregates [47]. Exposure to nitrite inhibited biofilm formation by Staphylococcus aureus, presumably through generating NO and inducing dispersal [48].…”
Section: No-mediated Dispersal Is Conserved Across Speciesmentioning
confidence: 99%